John H. Cherry, Digest of the Laws and Ordinances of the City of Little Rock, with the Constitution of the State of Arkansas; General Incorporation Laws; and All Acts of the General Assembly Relating to the City 168 (1882) - (:unkn) unknown (My University, 1881)
Prohibited the concealed carry of any pistol, colt, slung-shot, cross-knuckles, knuckles of lead, brass, or other metal, or Bowie-knife, dirk-knife, dirk, dagger, any knife resembling a Bowie-knife, or any other dangerous or deadly weapon. Violators guilty of a misdemeanor, fined not less than ten nor more than twenty-five dollars, and double that sum for each subsequent offense.
Keywords: CARRY - CONCEALED